p(x)=6x-5

Simple and best practice solution for p(x)=6x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for p(x)=6x-5 equation:


Simplifying
p(x) = 6x + -5

Multiply p * x
px = 6x + -5

Reorder the terms:
px = -5 + 6x

Solving
px = -5 + 6x

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Divide each side by 'x'.
p = -5x-1 + 6

Simplifying
p = -5x-1 + 6

Reorder the terms:
p = 6 + -5x-1

See similar equations:

| 3x-2y=-33 | | f(x)=3x^2-24x+20 | | ln(x-2)-ln(x-11)=ln(x-1)-ln(x+14) | | 8x+[20-(3x-11)]=-6+4(2-6x) | | 14x+5=3(-x+3)-11 | | 42t^2-100t+50=0 | | -5(2x+5)=-25 | | 26-8x=3[2-4(x-7)] | | -10(s+3)=-62 | | -4=-8+4x | | 2y-8x=-2 | | 3(3x+7)=66 | | 5(2x+8)=120 | | 1.5d+3.25=1+22.5 | | 144/((72/4)/6) | | -13+3x=52+24x | | 2a(a-2)x=a-2 | | 313=-16t^2+153t+3 | | -5x-6=-42 | | x-3=46-6x | | 6x-4=-58 | | p(x)=6x^4-18x^3+6x^2-30x+36 | | Q=1/2P-4 | | 25+30x=295 | | D(x)=x^7+2*x^5+5*x | | 7x-5=-37+3x | | 3(4+4)= | | -58=x-7x+8 | | 3(4*3)= | | 3x^3-5x=2x^2+6 | | y^2-3y-44=0 | | 10n^2+11n+3=0 |

Equations solver categories